Chapter Introduction - Zhao, Wei (Taylor & Francis, 2023)
Starting with a true story that inspired this research, the introduction raises the main research questions that are examined and addressed in the rest of the book: how have different forms of traditions affected the physical, psychological, and social constructions of home for people living in vernacular settlements in rural China? The introduction frames the study within the scholarly understandings of the concepts of home, place, and tradition. It identifies the gap in the existing scholarship of home when contextualizing it in the place of rural China and considering attributes of Chinese cultural traditions. Finally, it introduces Yanxia village as the case study and summarizes the research process and method. In particular, it outlines the validity of adopting the method of photovoice, which includes over 600 photographs taken by the residents along with the collection of the life stories behind these photographs.